MANAJEMEN KUALITAS LAYANAN USAHA MIKRO PADA SENTRA BATIK GAJAH OLING BANYUWANGI - Azkiya, Ahmad Azkal; Aliya, Mahya (Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze service quality management in micro-enterprises at the Gajah Oling Batik Center in Banyuwangi using a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observations, and documentation involving business owners, stakeholders, and consumers. The findings reveal that service quality is strongly influenced by the diverse perspectives of business owners and the varying expectations of consumers. Local consumers tend to evaluate services based on emotional closeness and personal communication, whereas tourists demand greater professionalism, clearer information, and better-organized product displays. Analysis using the KUALITAS LAYANAN dimensions indicates that empathy is the primary strength of culturally rooted services, while tangibles, responsiveness, and assurance still vary significantly. The study concludes that improving service quality requires strengthening the capacity of micro-entrepreneurs, integrating cultural values into modern service standards, and enhancing collaboration among stakeholders to produce more consistent and competitive services.